E-learning with Camtasia Ctudio : a step-by-step guide to producing high-quality, professional E-learning videos for effective screencasting and training - Demyan, David B. (Community experience distilled., 2014)
Chapter 2: Planning the Project; What is a project plan?; Why is planning important?; What will a plan accomplish?; Selecting the subject; Defining project scope; Setting project goals; Be specific; Resources; What resources will I need?; The project team; The review team; Software and systems; Learner analysis; Informal learner analysis; Formal learner analysis; The project outline; The subject outline; The detailed outline; How much detail should I include?; Using the project plan; Modifying the project plan; Try it - create a project plan; Summary; Chapter 3: Creating the Script.